The yeast vacuolar membrane proteome - Wiederhold, E.; Gandhi, T.; Permentier, H.P.; Breitling, R.; Poolman, B.; Slotboom, D.J.
Transport of solutes between the cytosol and the vacuolar lumen is of crucial importance for various functions of vacuoles, including ion homeostasis, detoxification, storage of different molecules such as amino acids, phosphate and calcium ions, and proteolysis. In order to identify proteins that catalyze solute transport across the vacuolar membrane, the membrane proteome of purified Saccharomyces cerevisiae vacuoles was analyzed. Subtractive proteomics was used to distinguish contaminants from true vacuolar proteins by comparing the relative abundances of proteins in pure and crude preparations. A robust statistical analysis combining Enrichment Ranking with the double-boundary iterative Group Analysis revealed that 148 proteins were significantly enriched in the pure vacuolar preparations. Among these proteins were well-characterized vacuolar proteins, such as the subunits of the V-ATPase, but also proteins that had not previously been assigned to a cellular location, many of which are likely novel vacuolar membrane transporters e.g. for nucleosides and oligopeptides. Although the majority of contaminating proteins from other organelles were depleted from the pure vacuolar membranes, some proteins annotated to reside in other cellular locations were enriched along with the vacuolar proteins. In many cases the enrichment of these proteins is biologically relevant, and we discuss that a large group is involved in membrane fusion and protein trafficking to vacuoles and may have multiple localizations. Other proteins are degraded in vacuoles and in some cases database annotations are likely to be incomplete or incorrect. Our work provides a wealth of information on vacuolar biology and a solid basis for further characterization of vacuolar functions.
Keywords: ORGANELLE PROTEOMICS; VACUOLE; MEMBRANE PROTEINS; ITERATIVE GROUP ANALYSIS; MEMBRANE TRANSPORT